In defense of monopoly : how market power fosters creative production - McKenzie, Richard B.; Lee, Dwight R. (University of Michigan Press, 2008)
In Defense of Monopoly offers an unconventional but empirically grounded argument in favor of market monopolies. Authors McKenzie and Lee claim that conventional, static models exaggerate the harm done by real-world monopolies, and they show why some degree of monopoly presence is necessary to maximize the improvement of human welfare over time. Inspired by Joseph Schumpeter's suggestion that market imperfections can drive an economy's long-term progress, In Defense of Monopoly defies conventional assumptions to show readers why an economic system's failure to efficiently allocate its resources is actually a necessary precondition for maximizing the system's long-term performance: the perfectly fluid, competitive economy idealized by most economists is decidedly inferior to one characterized by market entry and exit restrictions or costs.